Teaching English or Teaching the West? Multimodal Cultural Imperialism in Big Show Level 5 Textbooks Used in Indonesian Islamic Montessori Schools - Muhammad Arif; Qurrata’ain; Greis Evalinda; Ida Nyoman Tri Darma Putra (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study extends Critical Discourse Analysis (CDA) beyond traditional textual examination to investigate multimodal representations of culture in "Big Show Teacher’s Guide Level 5" a 135-page English as a Foreign Language (EFL) textbook guidance for teachers, widely used in Indonesian educational contexts, particularly Islamic Montessori elementary schools. Employing an expanded analytical framework incorporating five dimensions which are visual-spatial representation, digital multimodality, embodied cultural practices, temporal-contextual positioning, and material-environmental factors. The study reveals systematic patterns of cultural imperialism operating through multiple semiotic modes simultaneously. Analysis of all twelve units demonstrates that while the textbook superficially incorporates cultural variety, it fundamentally privileges Western cultural norms, consumer values, and secular worldviews that conflict with Indonesian communitarian values, Islamic principles, and indigenous knowledge systems. The study documents how 4th of July celebrations, London landmarks, and Western leisure activities are positioned as universal references while Indonesian Independence Day, traditional markets, indigenous games, and local wildlife remain entirely absent. Material requirements including extensive technology access create class-based educational exclusion, while rigid temporal structures contradict Islamic prayer schedules and traditional learning rhythms. These findings demonstrate that genuine educational equity requires comprehensive multimodal redesign across all five dimensions, not superficial textual modifications.